The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/molecules21121683
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Fluorescence Quenching in the Electron Transfer Photooxidation of Nucleobase-Related Azetidines by Cyanoaromatics

Abstract: Electron transfer involving nucleic acids and their derivatives is an important field in bioorganic chemistry, specifically in connection with its role in the photo-driven DNA damage and repair. Four-membered ring heterocyclic oxetanes and azetidines have been claimed to be the intermediates involved in the repair of DNA (6-4) photoproduct by photolyase. In this context, we examine here the redox properties of the two azetidine isomers obtained from photocycloaddition between 6-aza-1,3-dimethyluracil and cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 24 publications
(37 reference statements)
4
13
0
Order By: Relevance
“…This value is compatible with that reported for the cis , syn ‐cyclobutane dimers of 1,3‐dimethythymine . By contrast, two waves were observed for the oxidation of the dyad AZT m ; the first one, with a peak potential E p (1) at about 1.34 V (close to the E p of the azetidine formed between 6‐azauracil and cyclohexene), and the second one E p (2) at about 1.93 V. This latter peak is similar to that observed for the azaU m ‐T m dyad (see the Supporting Information), which might be formed during the experiment as a product of the photo‐oxidation process . Concerning, T m <>T m , a single wave was observed, with an E p of 1.85 V, which was in agreement with the previously reported value of 1.83 V (vs. Ag/AgCl) …”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…This value is compatible with that reported for the cis , syn ‐cyclobutane dimers of 1,3‐dimethythymine . By contrast, two waves were observed for the oxidation of the dyad AZT m ; the first one, with a peak potential E p (1) at about 1.34 V (close to the E p of the azetidine formed between 6‐azauracil and cyclohexene), and the second one E p (2) at about 1.93 V. This latter peak is similar to that observed for the azaU m ‐T m dyad (see the Supporting Information), which might be formed during the experiment as a product of the photo‐oxidation process . Concerning, T m <>T m , a single wave was observed, with an E p of 1.85 V, which was in agreement with the previously reported value of 1.83 V (vs. Ag/AgCl) …”
Section: Resultssupporting
confidence: 61%
“…To interpret the excited‐state quenching of Phs by AZT m , four Phs with significantly different redox properties of the singlet excited state were chosen to perform a quantum‐chemistry determination of the photoreduction and photo‐oxidation energetics: 1‐MN and DCN (used in the experiments detailed above), together with TMPD and cyanonaphthalene (CNN), employed in previous works ,. Singlet‐excited‐state redox potentials of E *=−2.5, 2.4, −3.3, and 1.4 V versus Ag/AgCl were obtained, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 While the relative stereochemical conguration of the azetidine products was not assigned by Swenton, the Miranda group completed the stereochemical assignment of the azetidine products 24 from the cycloaddition reaction between 21 and cyclohexene, one of the compounds Swenton and coworkers initially reported. 28 Similarly, Wamhoff and coworkers found that the cycloaddition reaction between 21 and dihalomaleamides proceeded in excellent stereoselectivity, giving exclusively the endo diastereomer (25). 29 The Ohta group demonstrated that 9-cyanophenanthridine (26) undergoes a [2 + 2] cycloaddition with anethole (27) under irradiation with UV light (Fig.…”
Section: Scope and Limitationsmentioning
confidence: 99%
“…Similarly, heterocyclic oxetanes and azetidines have been suggested as intermediates involved in the photorepair of the thymine-cytosine (6-4) photoproduct by photolyases [ 45 , 46 ], but contrary to the oxetanes, the oxidative and reductive properties of the azetidines have received less attention. In their study, Fraga-Timiraos et al [ 47 ] synthesized two azetidine isomers, which the authors use to model the initial electron transfer step in the photorepair of thymine-cytosine (6-4) photoproducts by photolyases. By performing a series of steady-state and time-resolved fluorescence quenching experiments with photoreductants and photooxidants, the authors evaluate the effect that cis , trans stereochemistry has on the redox properties of the azetidine isomers and on their electron transfer efficiency.…”
mentioning
confidence: 99%